2018
DOI: 10.1159/000494988
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Signaling in Post-Stroke Fatigue and Depression

Abstract: Background: In the United States, stroke continues to be the cause for long-term disability. Of the patients with a first stroke, up to 75% will experience post-stroke fatigue (PSF) in the first year following stroke. PSF is one of the most disabling symptoms in stroke survivors; it decreases quality of life, increases mortality, and is a barrier to stroke rehabilitation. Given the incidence of stroke and the prevalence and detrimental impact of PSF on quality of life, independent living, and overall survival,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 122 publications
0
51
0
1
Order By: Relevance
“…Etiology of the PSD is considered multifactorial, a combination of biological and environmental factors; in this sense one of the most supported biological hypotheses currently is related with the participation of inflammatory mediators. 22 In this sense it has been shown that the proinflammatory environment increases the activation of the KP in the CNS. 23,24 However, the neurobiological relevance of this route lies mainly in that there is evidence that some of its intermediate metabolites have redox and neuroactive properties, modulating glutamatergic, cholinergic, and dopaminergic neurotransmission.…”
Section: Discussionmentioning
confidence: 99%
“…Etiology of the PSD is considered multifactorial, a combination of biological and environmental factors; in this sense one of the most supported biological hypotheses currently is related with the participation of inflammatory mediators. 22 In this sense it has been shown that the proinflammatory environment increases the activation of the KP in the CNS. 23,24 However, the neurobiological relevance of this route lies mainly in that there is evidence that some of its intermediate metabolites have redox and neuroactive properties, modulating glutamatergic, cholinergic, and dopaminergic neurotransmission.…”
Section: Discussionmentioning
confidence: 99%
“…Post-stroke fatigue (PSF) is a common and lasting sequela after stroke. Of the patients with a first stroke, up to 75% will suffer PSF in the first year following stroke [1]. PSF has a detrimental impact on the recovery of neurological function, quality of life and rehabilitation of stroke survivors [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence points to systemic inflammatory responses and sickness behaviour induced by pro-inflammatory cytokines as important factors in post-stroke fatigue. 37 To date, there are no human studies on the role of HMGB1 in post-stroke fatigue. However, in an experimental animal stroke model, it was observed that the release of HMGB1 and signalling through RAGE contributed to brain injury–induced sickness behaviour.…”
Section: Discussionmentioning
confidence: 99%